IT governance enablers in relation to IoT implementation: a systematic literature review - Henriques, D.; Pereira, R.; Almeida, R.; da Silva, M. M. (Digital Policy, Regulation and Governance, 2019)
Purpose The purpose of this paper is to obtain a list of recommendations addressed by the information technology (IT) governance enablers in relation to IoT implementation. The reason behind this it is the lack of information about these instances which could the organizations to be more effective when implementing IoT. Design/methodology/approach The objectives will be obtained using the methodology - systematic literature review. Findings During the research, a list of recommendations was created on each IT governance enabler in relation to IoT implementation, showing the flaws that exist at the literature level for each enabler. Originality/value The state of art of this research is a creation of a list of recommendations according to IT governance enablers to be applied on an IoT implementation.